Unveiling the Rarity: A Case Report on Distal Femur Parosteal Osteosarcoma (Journal of Pakistan Orthopaedic Association, 2024)
The parosteal osteosarcomas represents a rare low grade malignant but less metastasizing tumour. They often present with a simulating clinic-radiological features of other similar conditions like osteochondroma. Local wide Excision with hemi-cortical resection usually behaves better without recurrence. We are unveiling one of such case who reported with progressively increasing swelling, pain in popliteal fossa and difficulty on squat for the last 2 years. Its location at distal femoral metaphysis and radiographic appearance was little confusing for osteochondroma. Whereas MRI findings suggested it as of a parosteal osteosarcoma. The wide local excision was successful with no recurrence at 2 years of follow-up.